Análise morfotectônica da Bacia do rio Santo anastácio, sp, através de parâmetros fluviomorfométricos e de registros paleossísmicos - Guedes, Ivan Claudio [UNESP]; Etchebehere, Mario Lincoln de Carlos; Morales, Norberto [UNESP]; Stevaux, José Cândido; Santon, Gisele de Cássia [UNESP] (My University, 2009)
Fluvial morphometry is method of great value regarding neotectonic analysis of extensive areas because streams, besides representing one of the main agents in the relief modeling, quickly adjust their thalwegs to even the most gentle crustal deformations. The purpose of this paper is to present the application of some morphometric techniques in the Santo Anastácio River hydrographic basin in order to identify recent tectonic deformations. Additionally, we show liquefaction structures identified in the basin and interpreted here as seismites linked to ancient earthquakes (magnitudes greater than 5). The morphometric survey includes longitudinal stream profile analysis, RDE (declivity versus stream length) index application, and the sinuosity study of the Santo Anastácio River channel. Geologic substrate comprises Cretaceous siliciclastic rocks of the Caiuá and Bauru groups, locally covered by Cenozoic sediments (alluvial plains, terrace deposits, colluvial aprons, as well as in situ regoliths). Considering that liquefaction structures affect dark clay layers of 32.340±320 year BP age (14C dating), a lower age limit for the ancient earthquake is triggered in that region. The authors believe that neotectonic understanding of the Western São Paulo State Plateau is important to the geologic and geomorphologic evolution of that landscape and to the consequent territorial planning and occupation.

Registros morfométricos das drenagens tem se mostrado de grande valia no que concerne aos estudos empregados para detecção de deformações neotectônicas, uma vez que os cursos d’água tendem a se ajustar rapidamente às deformações crustais, mesmo ante aquelas mais sutis, representando um dos principais agentes de modelagem do relevo. Esta característica os tornam importantes para os estudos envolvendo a neotectônica. O propósito deste artigo é apresentar a aplicação dos Perfis Longitudinais das Drenagens, o índice RDE (Relação Declividade vs. Extensão) e a análise da sinuosidade do rio Santo Anastácio, com o objetivo de delinear áreas sujeitas a deformações neotectônicas. Adicionalmente, também são apresentadas as estruturas de liquefação (sismitos) identificadas na bacia do rio Santo Anastácio como fortes indicadores de atividade neotectônica. Considerando que as estruturas de liquefação afetam camadas de argila escura (32.340+320 anos A.P. por datação 14C), entende-se que o eventual sismo que as tenha gerado teria ocorrido aquém de tal data. A bacia do rio Santo Anastácio está inserida no contexto do Planalto Ocidental Paulista e apresenta um substrato rochoso cretáceo abarcando os grupos Caiuá e Bauru e sedimentos cenozóicos. O entendimento da neotectônica nesta área faz-se de suma importância para avaliação do risco sísmico, para planejamento territorial, e para o entendimento da história evolutiva da paisagem nesta porção do território paulista. Palavras-chave: neotectônica, paleossimologia, bacia do rio Santo Anastácio, morfometria fluvial.
Morphotectonic analysis of the santo anastácio hydrographic basin, state of São Paulo, southeastern Brazil, using fluvial morphometry and paleoseismic features
Keywords: Fluvial morphometry; Neotectonics; Paleoseismology; Santo anastácio; Cenozoic; Cretaceous; crustal deformation; fluvial geomorphology; hydrographic survey; liquefaction; morphometry; paleoseismicity; plateau; relief; river basin; seismite; siliciclastic deposit; substrate; tectonic evolution; thalweg; Brazil; Sao Paulo [Brazil]